Optimalisasi Keamanan Nasional: Pentingnya Keterlibatan Sektor Swasta dalam Industri Pertahanan Indonesia - Ratu Syra Quirinno; Suwito, Suwito; Lukman Yudho Prakoso (CV. AFDIFAL MAJU BERKAH, 2024)
This journal discusses about the current condition of Defense Industry in Indonesia, the strategic role of the private sector in enhancing Indonesia's national security through its participation in the defense industry. The main focus of the research using this literature study is to analyze the positive impact of private sector involvement in optimizing resources, technology and innovation to strengthen national defense resilience. Private defense companies can also be a source of raising funds both from abroad and domestically to build production infrastructure, finance research and development, which is able to develop domestic defense industry capabilities and have a positive impact on national resilience. The development of private companies in the defense sector can have other positive effects, namely giving rise to competition in procurement contracts which are usually dominated by state-owned companies and large international defense companies, so that the contract process can run with more options but still be produced. domestically. Based on defensenews data, the majority of the top one hundred defense companies are private companies, this is one of the considerations in building Indonesian national resilience, especially in developing defense technology that has global competitiveness. By highlighting the benefits of collaboration between government and the private sector, this journal contributes to designing policies that support effective integration between the two. The results of this research can serve as a basis for strengthening strategic partnerships and achieving more resilient national security goals.